O duplo aspecto das emoções na Campanha Televisiva Lula Presidente - Silva, Ricardo Rifane da (2007)
This study interprets the broadcast campaign “Lula for President”, as shown on the Free Timetable for Electoral Propaganda in the year 2002, delimiting the analysis on the moments strongly marked by the presence of emotional contents. It describes some full programs as well some fragments of others, intending to seize the mechanisms of the expression of variable feelings. It compares the corpus with the historical context, relating the emotions inside the programs and electoral strategies. It defines two basic modes in strategy that comprehend the collected material. Utilizes theory and methodological resources of the Anthropology of Performances as well Semiotic notions.